2016
DOI: 10.1016/j.jid.2016.04.036
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Defect in Keratinocyte Function Leads to Inflammation in Hidradenitis Suppurativa

Abstract: Hidradenitis suppurativa (HS) is a chronic, inflammatory, debilitating, follicular disease of the skin. Despite a high prevalence in the general population, the physiopathology of HS remains poorly understood. The use of antibiotics and immunosuppressive agents for therapy suggests a deregulated immune response to microflora. Using cellular and gene expression analyses, we found an increased number of infiltrating CD4(+) T cells secreting IL-17 and IFN-γ in perilesional and lesional skin of patients with HS. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
205
1
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(226 citation statements)
references
References 48 publications
15
205
1
5
Order By: Relevance
“…Our immunohistochemical analysis revealed that the IL‐36 cytokines are expressed primarily by keratinocytes (Fig. ), which are primary skin cells responding to innate immune stimuli, and accumulating data demonstrate an important role within the inflammatory loop in HS . A hypothesis of an overactive immune system of the follicular epithelium in patients with HS has been formulated .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our immunohistochemical analysis revealed that the IL‐36 cytokines are expressed primarily by keratinocytes (Fig. ), which are primary skin cells responding to innate immune stimuli, and accumulating data demonstrate an important role within the inflammatory loop in HS . A hypothesis of an overactive immune system of the follicular epithelium in patients with HS has been formulated .…”
Section: Discussionmentioning
confidence: 99%
“…A hypothesis of an overactive immune system of the follicular epithelium in patients with HS has been formulated . Keratinocytes isolated from hair follicles of patients with HS showed an altered antimicrobial peptide (AMP) pattern after in vitro stimulation with microbial products and enhanced secretion of proinflammatory mediators …”
Section: Discussionmentioning
confidence: 99%
“…To this end, we investigated the expression of LL‐37 and CAMP in HS, PS, AD and healthy skin by immunohistochemistry and semi‐quantitative real‐time PCR and compared whether LL‐37 peptide and CAMP mRNA levels correlate with lesional HS skin. In addition, we examined what kind of cells (T cells, macrophages and neutrophils) and cytokines (IFN‐γ, IL‐17, IL‐23, IL‐32, IL‐1β, TNF‐α and IL‐10), which are known to be elevated in HS correlate with the presence of LL‐37. To complete our analysis, we investigated the impact of LL‐37 on the proliferation of lectin‐stimulated CD4 + and CD8 + T cells isolated from the blood of healthy donors and patients with HS and delineated by calcium assay, how LL‐37 impacts proliferation of T cells directly.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, one could check how administration of lipophagy inhibitors such as chloroquine, Atglistatin and Lalistat or silencing key autophagy proteins (ATG5) strictly in DAs prior to coculture with human HFs can impact upon anagen‐catagen transformation (considerations prior to experimental design are detailed in Text ). Multiplex platforms may also be employed to check whether DAs engage in secretion of candidate hair growth–modulatory agents during lipophagy inhibition . Additionally, autophagy could be promoted in DAs using commercially available nutritional supplements containing spermidine to investigate how upregulating DA autophagy in human skin can impact upon human HFs …”
Section: How To Test the Hypothesismentioning
confidence: 99%